Pertanggungjawaban Tindak Pidana Pemilihan Umum yang Dilakukan Panitia Pemilihan Kecamatan (PPK) : Studi Putusan Pengadilan Negeri Medan Nomor 1/Pid.S/2024/PN MDN - Tunggul Prasetia Rambe; Muhammad Ridwan Lubis (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
This research is motivated by the rampant institutional pathology within election management, specifically the criminal act of vote manipulation involving ad-hoc election organizers. The focus of the study is directed at the case of vote tampering during the 2024 Legislative Election by three members of the Medan Timur Sub-district Election Committee (PPK). This study aims to analyze the construction of official criminal liability in election offenses, dissect the legal reasoning (ratio decidendi) of the judges in imposing sanctions, and identify the operational constraints faced by the PPK in the field. This normative legal research utilizes a statutory approach, a case approach, and a conceptual approach, focusing primarily on the written document of the Medan District Court Decision Number 1/Pid.S/2024/PN Mdn. The results indicate that the mechanism of criminal liability against the three active commissioners of PPK Medan Timur met the elements of actus reus in the form of physical manipulation of numerical recapitulation data and mens rea in the form of direct intent (dolus directus) to alter political party votes collectively (Article 55 Paragraph 1 to-1 of the Criminal Code). The legal standing of the perpetrators as active election organizers triggered the specific statutory aggravation clause of an additional one-third sanction (delictum proprium) under Article 554 of Law Number 7 of 2017 concerning Elections, based on the principle of breach of public trust.